Rapid acoustofluidic mixing by ultrasonic surface acoustic wave-induced acoustic streaming flow - Beomseok Cha; Song Ha Lee; Syed Atif Iqrar; Hee-Gyeong Yi; Jangho Kim; Jinsoo Park (Ultrasonics Sonochemistry, 2023)
Ultrasonic surface acoustic wave (SAW)-induced acoustic streaming flow (ASF) has been utilized for microfluidic flow control, patterning, and mixing. Most previous research employed cross-type SAW acousto-microfluidic mixers, in which the SAWs propagated perpendicular to the flow direction. In this configuration, the flow mixing was induced predominantly by the horizontal component of the acoustic force, which was usually much smaller than the vertical component, leading to energy inefficiency and limited controllability. Here, we propose a vertical-type ultrasonic SAW acousto-microfluidic mixer to achieve rapid flow mixing with improved efficiency and controllability. We conducted in-depth numerical and experimental investigations of the vertical-type SAW-induced ASF to elucidate the acousto-hydrodynamic phenomenon under varying conditions of total flow rate, acoustic wave amplitude, and fluid viscosity conditions. We conducted computational fluid dynamics simulations for numerical flow visualization and utilized micro-prism-embedded microchannels for experimental flow visualization for the vertical SAW-induced ASF. We found that the SAW-induced vortices served as a hydrodynamic barrier for the co-flow streams for controlled flow mixing in the proposed device. For proof-of-concept application, we performed chemical additive-free rapid red blood cell lysis and achieved rapid cell lysis with high lysis efficiency based on the physical interactions of the suspended cells with the SAW-induced acoustic vortical flows. We believe that the proposed vertical-type ultrasonic SAW-based mixer can be broadly utilized for various microfluidic applications that require rapid, controlled flow mixing.